Guest Editorial Introduction to the Special Section on Image Management in the Healthcare Enterprise. - Mun, S. K. (IEEE Transactions on information technology in biomedicine)
The eleven articles in this special section are devoted to the subject of image management in the healthcare enterprise. This editorial reviews the evolution of image management in the radiology community over the past 20 years and briefly summarizes the articles included in the special section.